Metamorphosis of a butterfly: Neo-liberal subjectivation and queer autonomy in Xiyadie's papercutting art. (1st September 2019) - Bao, Hongwei
AbstractCelebrated as 'China's Tom of Finland', Xiyadie is probably one of the best-known queer artists living in China today. His identity as a gay man from rural China and his method of using the Chinese folk art of papercutting for queer artistic expression make him a unique figure in contemporary Chinese art. As the first academic article on the artist and his works, this article examines Xiyadie's transformation of identity in life and his representation of queer experiences through the art of papercutting. Using a critical biographical approach, in tandem with an analysis of his representative artworks, I examine the transformation of Xiyadie's identity from a folk artist to a queer artist. In doing so, I delineate the transformation and reification of human subjectivity and creativity under transnational capitalism. Meanwhile, I also seek possible means of desubjectivation and human agency under neo-liberal capitalism by considering the role of art in this picture. This article situates Xiyadie's life and artworks in a postsocialist context where class politics gave way to identity politics in cultural production. It calls for a reinvigoration of Marxist and socialist perspectives for a nuanced critical understanding of contemporary art production and social identities.